2008
DOI: 10.1186/1471-2407-8-27
|View full text |Cite
|
Sign up to set email alerts
|

TP53 status and taxane-platinum versus platinum-based therapy in ovarian cancer patients: A non-randomized retrospective study

Abstract: BackgroundTaxane-platinum therapy (TP) has replaced platinum-based therapy (PC or PAC, DNA damaging chemotherapy) in the postoperative treatment of ovarian cancer patients; however, it is not always effective. TP53 protein plays a differential role in response to DNA-damaging agents and taxanes. We sought to define profiles of patients who benefit the most from TP and also of those who can be treated with PC.MethodsWe compared the effectiveness of PC/PAC (n = 253) and TP (n = 199) with respect to tumor TP53 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Therefore, evaluation of clinical importance of the studied polymorphisms was performed in all patients treated with taxane-platinum, and in subgroups determined by TP53 immunohistochemical status (TP53(K) and TP53(C)), in which TP53(C) means TP53 dysfunction manifested by TP53 protein accumulation; the latter had been determined previously (Kupryjańczyk et al 2008).…”
Section: Analysis Of Genetic and Non-genetic Parameters And Their Infmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, evaluation of clinical importance of the studied polymorphisms was performed in all patients treated with taxane-platinum, and in subgroups determined by TP53 immunohistochemical status (TP53(K) and TP53(C)), in which TP53(C) means TP53 dysfunction manifested by TP53 protein accumulation; the latter had been determined previously (Kupryjańczyk et al 2008).…”
Section: Analysis Of Genetic and Non-genetic Parameters And Their Infmentioning
confidence: 99%
“…Among cases, 69 patients were uniformly treated in gynecologic oncology units with standard taxaneplatinum regimens, as previously described (Kupryjańczyk et al 2008). Taxol, given in a 24 h (135 mg/m 2 ) or 3 h infusion (175 mg/m 2 ), or docetaxel (75 mg/m 2 ) was followed by cisplatin (75 mg/m 2 ) or carboplatin (AUC6).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In OC, p53 has been investigated in various studies in which a mutation rate between 23 and 80% has been found (Hollstein et al 1991(Hollstein et al , 1994Levine et al 1991;Levine 1997;Galic et al 2007;Kupryjanczyk et al 2008;Salani et al 2008). P53 mutations in OC have been related to poor prognosis (Wen et al 1999;Ueno et al 2006) as well as to better survival (Ueno et al 2006) but still no large scale prospective studies have been conducted to determine whether the p53 status is of definitive predictive value for survival.…”
Section: Discussionmentioning
confidence: 97%
“…Seminal studies revealed a significant correlation between p53 status and aneuploidy in advanced stage disease (6). Studies have revealed that p53 status (measured by p53 protein overexpression) correlated with favorable response to taxane-platinum based therapy (7). Therefore, loss of p53 function and ablation of the DNA-damage induced p53 -dependent apoptosis pathway is a strong predictor of taxane-platinum-based therapy.…”
Section: Introductionmentioning
confidence: 99%